Current Trends in the Financial Market Development - ZATSARINNYI, Еlena I.; MALYKH, Natalya I.; SEVERINA, Yulia N.; GENDON, Angelica L.; MINNULLINA, Anna Yu.; MALYSHENKO, Kostyantyn A. (Journal of Advanced Research in Law and Economics, 2018)
The paper shows that the modern tendencies of financial market based on the possibility of stratification and infrastructural development of the economy as a whole. The authors found that special attention should be given to development of infrastructural support from the state, and the formation of technological trends in the structure of public consumption. The article indicates that financial market conditions are set on the basis of the calculation of both financial and investment risks, which facilitate the effective use of capital. The authors note a trend in which the rapid processes of globalization have transformed the infrastructure of the financial market on one of the dominant redistribution of capital not only within national economies but also on a global scale. It is established that financial market participants form a functional component of infrastructure capacity because of accumulation of financial resources has a functional purpose. The functional component of the infrastructural capacity of the financial market is in the process of transformation. This is a withdrawal from the market of a number of financial intermediaries, reduced the volume of assets of financial institutions, reduced demand for their services, which in the long run it will escalate the competition for the consumer between them. This will stimulate the emergence of new financial services and will contribute to the infrastructural capacity of the financial market.